Pengaruh Gaya Kepemimpinan, Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Perusahaan PT Pupuk Kalimantan Timur Departemen Pemasaran Sulawesi Selatan - Amanda Lady Virgo amanda (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to analyze the effect of leadership style, work motivation and work environment on employee performance at PT Pupuk Kalimantan Timur in the marketing office of Makassar, South Sulawesi. This type of research is quantitative, and the method of data collection in this study is to use a questionnaire. The sample as well as respondents in this study were 106 employees. The population in this study were all employees of the South Sulawesi marketing office of PT Pupuk Kalimantan Timur, covering the regions of Bone, Gowa, Sinjai, Makassar, Palakka etc. The method of analysis in this study uses the SPSS 21.00 program. The results of this study indicate that, first, there is an influence of leadership style on employee performance at PT PKT's marketing department in South Sulawesi. Second, there is an effect of employee motivation on employee performance at the PT PKT company in the marketing department of South Sulawesi. Third, the influence of the work environment on the performance of employees at the company PT PKT marketing department of South Sulawesi. Fourth, that leadership style, motivation and work environment affect employee performance in the company. This research is able to provide benefits for companies to improve the efficiency of employee performance and the quality of human resources in the company, especially those related to leadership style, motivation and work environment as well as employee performance.